EFEKTIFITAS PENEGAKAN HUKUM TERHADAP PERTAMBANGAN EMAS TANPA IZIN (PETI) DI WILAYAH HUKUM KEPOLISIAN RESOR GUNUNG MAS - Tri Wibowo; Mutia Evi Kristhy; Syamhudian Noor (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2024)
Several factors that encourage the large number of illegal mining include economic factors, lack of job availability and low economic status as the reasons for people to maintain work as illegal miners. Regarding law enforcement against mining activities that are suspected of violating the rules, it is still not optimal and the PETI problem is also a problem that has not found a good solution when viewed from several factors that determine the effectiveness or ineffectiveness of law enforcement, especially against Illegal Gold Mining (PETI) in the jurisdiction of the Gunung Mas Police, Central Kalimantan Province. This study uses an empirical legal research type, using a sociological legal approach. conclude that the Effectiveness of Law Enforcement against Illegal Gold Mining (PETI) in the jurisdiction of the Gunung Mas Police Resort based on research with various prevention efforts in the form of preventive efforts to repressive efforts in the form of action against Illegal Gold Mining (PETI) in general can be said to be ineffective considering that in fact the existence of Illegal Gold Mining (PETI) is still rampant and massive in the jurisdiction of the Gunung Mas Police Resort as supporting factors for the effectiveness of law enforcement such as the substance of the law which is still unclear and has not been implemented properly, Legal structure factors such as implementing apparatus for various provisions of legal regulations that have not been maximized in implementation such as the lack of intensive and sustainable socialization, and Community factors such as community economic factors which are the dominant factor as a factor causing the massive Illegal Gold Mining (PETI) as has been clearly described in the explanation section of this Research. This study also found several obstacles in Law Enforcement against Illegal Gold Mining (PETI) in the jurisdiction of the Gunung Resort Police based on research that the obstacles consist of internal obstacles originating from within the Police at the Gunung Mas Resort Police, such as the lack of supporting Facilities and Infrastructure such as the number of Police Posts and Sector Police, the lack of the number of POLRI members / personnel in the jurisdiction of the Gunung Mas Resort Police, as well as from the dominant external factor, namely the lack of good coordination between the Gunung Mas Resort Police and related parties such as the Gunung Mas Regency Government and various related Agencies.